2020
DOI: 10.1167/tvst.9.4.24
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Platelet Lysate Compared to Autologous and Allogeneic Serum Eye Drops

Abstract: Platelet lysate produced from platelet apheresis components has been proposed as an alternative to serum eye drops in the treatment of ocular surface disease. This study compared the effects of platelet lysate and serum on growth factor, cytokine and nanoparticle concentrations, and corneal epithelial cell proliferation. Methods: The concentration of growth factors, cytokines, and nanoparticles in platelet lysates manufactured from either fresh or expired platelet apheresis concentrations collected with Trima … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…To minimize irregularity caused by batch-batch variation in the scratch wound assay, we used 5% CCP4 and showed that hPL significantly increased the rate of wound closure compared to FBS. Our results are consistent with previous published results 27 , 28 showing hPL has a positive effect on epithelial cell proliferation and wound healing. These findings also suggest that standard preparation protocols and strict quality control is essential when using hPL in cell culture.…”
Section: Discussionsupporting
confidence: 94%
“…To minimize irregularity caused by batch-batch variation in the scratch wound assay, we used 5% CCP4 and showed that hPL significantly increased the rate of wound closure compared to FBS. Our results are consistent with previous published results 27 , 28 showing hPL has a positive effect on epithelial cell proliferation and wound healing. These findings also suggest that standard preparation protocols and strict quality control is essential when using hPL in cell culture.…”
Section: Discussionsupporting
confidence: 94%
“…It has been used to produce sponge-like dressings, 124 scaffolds, 125 bioactive gels, 126,127 and eye drops. 128,129 Recently, a core-shell structure particle-based dressing was designed with a calcium alginate shell and embedded in an alginate matrix. 130 PL and an antibiotic were loaded in the external matrix as active components for the treatment of chronic skin ulcers.…”
Section: Growth Factorsmentioning
confidence: 99%
“…In comparison with platelet‐rich plasma or platelet‐rich fibrin, PL has the advantage of limiting the variability of individuals. It has been used to produce sponge‐like dressings, 124 scaffolds, 125 bioactive gels, 126,127 and eye drops 128,129 . Recently, a core‐shell structure particle‐based dressing was designed with a calcium alginate shell and embedded in an alginate matrix 130 .…”
Section: Bioactive Moleculesmentioning
confidence: 99%
“…An increasing number of centers worldwide are producing serum eye drops from allogeneic blood donors, as highlighted in several publications, including in this journal [30][31][32][33][34]. Demonstrations have been recently provided that HPL produced from apheresis PC has high levels of growth factors and promotes corneal epithelial cell proliferation and wound healing at least as efficiently as serum [35]. Clinical data show the benefit of HPL prepared from allogeneic cord blood [36].…”
Section: Allogeneic Platelet Biomaterials For Regenerative Medicinementioning
confidence: 99%